Analisis Kinerja Jalan Tuanku Tambusai Pekanbaru ( Studi Kasus : Depan Mall Ska ) - Marbun, Douglas; Elianora, Elianora; Sandhyavitri, Ari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The degression of road performance was caused by several factors, particularly by road side activities. Tuanku Tambusai Road, the front side of Mall SKA is an economic region with large volume of traffic. This condition could be assumed in case the traffic volume gets higher, it will decrease the performance of road side, especially on busy hours due to the movement of vehicles to SKA Mall, the stopping public transportations, street vendors, and the parking motorcycles at road side. This research aims to evaluate the performance of Tuanku Tambusai Road, at the front of SKA Mall and find some solutions to overcome theproblems. The road performance analysis was based on Manual Kapasitas Jalan Indonesia (MKJI) 1997. The traffic data was collected from 3 days long, i.e. Saturday (3/2/2018), Sunday (4/2/2018) and Monday (5/2/2018). The results showed that busy hour was happened on Sunday at 12.45-13.45 WIB with Q = 2579,6 smp/hour, C = 3234 smp/hour dan DS = 0,80. Due to DS was higher than MKJI standard, which is DS < 0,75 some planning needs to be done in order to increase the performance of road. In order to reach the maximum standard, a specific lane was planned for vehicles which made their way into SKA Mall. The results showed that DS was able to meet MKJI standard, i.e. DS = 0,59.Keywords : Road Performance, MKJI 1997, Side Activities.